2016
DOI: 10.1007/s10620-016-4109-2
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Barrett’s Esophagus: A Familial and Population-Based Perspective

Abstract: Barrett's esophagus (BE) is intestinal metaplasia of the lower esophagus and a precursor lesion for esophageal adenocarcinoma (EAC). Both are important health issues as they have rising incidences in the Western world. Improving the management of BE relies on understanding the underlying biology of this disease, but the exact biological mechanisms have been difficult to determine. BE is generally thought to be an acquired condition that develops secondarily to chronic gastroesophageal reflux. However, multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Approximately 7% of cases of Barrett's esophagus (BE) or EAC occur within families. [24][25][26] Familial cases develop at an earlier age than sporadic EACs. 27,28 Other risk factors for EAC, such as regurgitation, smoking and obesity, are less prevalent among individuals with familial BE or EAC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 7% of cases of Barrett's esophagus (BE) or EAC occur within families. [24][25][26] Familial cases develop at an earlier age than sporadic EACs. 27,28 Other risk factors for EAC, such as regurgitation, smoking and obesity, are less prevalent among individuals with familial BE or EAC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…43,44 Genetic factors associated with EAC and clinical utility Up to one third of EAC may be hereditary and attributed to a combination of germline mutations, 45 although single mutations are associated with only a 20% increase in risk of EAC, at most. 26 However, the sharp increase in EAC incidence in many countries cannot be accounted for by changes in the population's genetic make-up over a timeframe of only 50 years. Genetic predisposition might account for some of the variation in geographical incidence of EAC.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a genetic component has been shown to be important. Several studies have indicated genetic variations in esophageal cancer . There is evident genetic predisposition to the disease due to inherited variants and the effects of acquired somatic variants.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated genetic variations in esophageal cancer. [1][2][3][4][5] There is evident genetic predisposition to the disease due to inherited variants and the effects of acquired somatic variants. To be able to understand the disease progress and genetic relevance, it is essential to collect, organize, distribute, analyze, and interpret genetic variations in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%